Sex‐specific pheromone responses in Caenorhabditis elegans - Wang, Chen (John Wiley and Sons Inc., 2019)

(untitled) (EMBO Rep)
The characterization of receptors for sex pheromones provides important clues for understanding the mechanisms controlling animal mating and reproduction. In this issue, Wan et al 1 identify a putative sex pheromone receptor, the G protein‐coupled receptor SRD‐1, acting in a single Caenorhabditis elegans olfactory neuron class, called AWA, to mediate male attraction to volatile sex pheromones. Like in other systems, C. elegans sex pheromone elicits sex‐specific responses even though sex pheromone activates sensory neurons of both sexes.